2017
DOI: 10.1161/circinterventions.116.004605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tibial Artery and Pedal Arch Patency by Angiography in Patients With Critical Limb Ischemia and Noncompressible Ankle Brachial Index

Abstract: Among patients with critical limb ischemia and noncompressible ankle brachial index results, the prevalence of occlusive tibial and pedal arch disease is very high. Toe brachial index <0.7 is more sensitive in diagnosing occluded and significantly stenotic tibial artery disease in these patients compared with ankle pulse volume recording.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The detection of a triphasic pedal Doppler arterial waveform with a handheld Doppler appears to provide stronger evidence for the absence of PAD. The same applies for measurement of a TBI, which makes the presence of PAD unlikely if it is ≥0.75 and provides additional information compared with the ABI, particularly in patients with severe PAD below the ankle . Unfortunately, toe pressures may also be falsely elevated by the same factors that affect ABI (including digital artery calcification).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of a triphasic pedal Doppler arterial waveform with a handheld Doppler appears to provide stronger evidence for the absence of PAD. The same applies for measurement of a TBI, which makes the presence of PAD unlikely if it is ≥0.75 and provides additional information compared with the ABI, particularly in patients with severe PAD below the ankle . Unfortunately, toe pressures may also be falsely elevated by the same factors that affect ABI (including digital artery calcification).…”
Section: Diagnosismentioning
confidence: 99%
“…The same applies for measurement of a TBI, which makes the presence of PAD unlikely if it is ≥0.75 20 and provides additional information compared with the ABI, particularly in patients with severe PAD below the ankle. 34 Unfortunately, toe pressures may also be falsely elevated by the same factors that affect ABI (including digital artery calcification). There is insufficient evidence to support the use of a single bedside diagnostic test for PAD that may be used for all patients with diabetes and foot ulceration.…”
Section: Rationalementioning
confidence: 99%
“…While pulse wave recording (PVR) analysis can be a mean of assessing limb perfusion; however, this was not widely available. Importantly, a recent study by Randhawa et al showed mild association between PVR and tibial patency . Because of this, many other technologies are available or being developed to assess perfusion including skin perfusion pressure, TcPO 2 , indocyanine green fluorescence angiography, and continuous subcutaneous oxygen sensors .…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis showed that >70% of the tibial vessels that were considered to be noncompressible were actually occluded or severely stenotic by angiography. 17 The current noninvasive modalities for limb perfusion assessment measure different aspects of perfusion, and each modality has unique limitations. For example, TcPo 2 measures oxygen tension, but SPP measures the capillary opening pressure.…”
Section: Pathophysiological Challenges Of the Abimentioning
confidence: 99%